Restoration in vitro of normal rates of very-low-density lipoprotein triacylglycerol and apoprotein B secretion in hepatocyte cultures from diabetic rats. - Duerden, J M (1993)
Hepatocytes derived from diabetic rats were cultured in serum-free Waymouth's medium containing various supplements, after an initial 4 h period during which the cells were allowed to attach to the culture dish in the presence of foetal-bovine serum (10%). After removal of serum, these cells secreted much less very-low-density lipoprotein (VLDL) apoprotein B (apoB) and triacylglycerol than those derived from normal rats when cultured for 24 h in the basal medium. Inclusion of oleate (0.75 mM) in the medium initially increased the output of apoB and triacylglycerol, but the rates remained lower than those observed in normal hepatocytes and declined to zero after 72 h. This time-dependent decline in VLDL output was prevented by addition of dexamethasone to the oleate-containing medium. Levels of apoB and triacylglycerol output characteristic of normal hepatocytes could only be completely restored, however, by further addition of a mixture of lipogenic substrates (lactate plus pyruvate) to the medium. Restoration of normal levels of VLDL secretion in diabetic hepatocytes in vitro by this means was accompanied by a normal inhibitory response of apoB and triacylglycerol output to short-term (24 h) treatment with insulin or glucagon. Exposure of the cells to insulin for 72 h enhanced the secretion of VLDL, whereas treatment with glucagon for the same period potentiated the original inhibitory effect. The defective secretion of VLDL apoB observed when diabetic hepatocytes were cultured in the basal medium for 24 h could also be rectified by inclusion of a mixture of oleate (0.75 mM), lactate (10 mM), pyruvate (1 mM), dexamethasone (1 microM) and insulin (78 nM) in the medium during the 4 h attachment period in the presence of serum. Under these conditions, the increase in the secretory response of triacylglycerol was not so pronounced.